The peripheral blood mononuclear cells preparation and the hematology of Varanus salvator - Jitkamol Thanasak (2022)
The objectives of this study were to evaluate the proper anticoagulants coated in blood-collecting tube for the peripheral blood mononuclear cells (PBMCs) isolation and to evaluate the proper culture temperature for the Varanus salvator’s PBMCs, in addition, the hematological characteristics also reported. The heparin treated blood (n = 10) and EDTA treated blood (n = 10) from Varanus salvator were obtained for PBMCs evaluation. The PBMCs obtained from the heparin treated blood was significantly higher than that of EDTA treated blood during the culture period (P < 0.05) indicated heparin would be more appropriated anticoagulant for blood collection. The PBMCs cultured under 37◦C and 27◦C were not significantly difference on first three days but 37◦C showed significantly higher effect in the following days (P < 0.05) indicated both temperatures can be used which 37◦C should be an optimal for PBMCs preparation. The peripheral blood cells of Varanus salvator (n = 49) were analyzed for hematological profiles and characteristics which the number of erythrocytes 1.19 ± 0.04 x 1012/L (1.17–1.35 x 1012/L) and WBC 2.41 ± 0.13 x 109/L (2.29–2.81 x 109/L) with absolute differential count of heterophils 0.92 ± 0.02 x 109/L (0.87–0.95 x 109/L), lymphocytes 1.17 ± 0.01 x 109/L (1.15–1.23 x 109/L), azurophils 0.40 ± 0.01 x 109/L (0.37–0.42 x 109/L), basophils 0.000 ± 0.001 x 109/L (0.004–0.011 x 109/L) and monocytes 0.027 ± 0.002 x 109/L (0.028–0.039 x 109/L). These results would play an important role on the cell immunological studies of the Varanus salvator in the future.